Peran Pendidikan Administrasi Perkantoran di Era Digital - Aulia, Lisa (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2023)
This writing aims to provide knowledge and understanding of office administration education in today's digital era. Especially related to the competence of managers in the field of office administration in the information age which is colored by digital technology. This study used a deductive approach. The method of discussion by observing the phenomenon of office administration activities that occur in the field then relates to the theory and various views expressed by experts in the field of administration and observers of technological developments, as well as training provided for employees, Office administration plays an active role in each organization because professional management of office administration will enable organizational leaders to get precise, accurate, and fast data, as a basis for decision making. The importance of the role of information in this digital era causing people to often refer to conditions like today as the information age. Departing from such a reality, every organization must position the field of office administration proportionally.